1999
DOI: 10.2139/ssrn.158412
|View full text |Cite
|
Sign up to set email alerts
|

Bias and Efficiency of Single vs Double Bound Models for Contingent Valuation Studies: a Monte Carlo Analysis

Abstract: The Dichotomous Choice Contingent Valuation Method (DC-CVM), both in the single and the double bound formulation, has been in the last years the most popular technique among practitioners of contingent valuation, due to its simplicity of use in data collection. The single bound procedure is easier to implement than the double bound, especially in data collection and estimation. On the other hand, it is well known that the double bound is more efficient than the single bound estimator. It remains to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…As sample sizes as low as 250–400 have been shown to be sufficient for the double and single double bound contingent valuation methods to perform well in well in giving point estimates for the parameters and of the mean WTP [ 9 , 10 ], we ensured we had a sample size of at least 1,400 households in each of the four regions. To select the survey sample, first, a three-stage stratified sampling method was used to identify survey respondents.…”
Section: Willingness To Pay Surveymentioning
confidence: 99%
“…As sample sizes as low as 250–400 have been shown to be sufficient for the double and single double bound contingent valuation methods to perform well in well in giving point estimates for the parameters and of the mean WTP [ 9 , 10 ], we ensured we had a sample size of at least 1,400 households in each of the four regions. To select the survey sample, first, a three-stage stratified sampling method was used to identify survey respondents.…”
Section: Willingness To Pay Surveymentioning
confidence: 99%
“…Generally, CVM studies require large sample size because of large variation in WTP responses Mitchell and Carson (1989). Calia and Strazzera (1998) recommended 100 or less samples as small size , 250 -400 as medium size ; and more than 1000 as large size . The study also concluded that medium sample size performed well in both single and double bound CVM method for providing point estimates for the parameters and of the mean WTP.…”
Section: Survey Designmentioning
confidence: 99%
“…For applications see for instance McLeod and Bergland (), Calia and Strazzera (), Yoo and Chae (), Whitehead (), Loureiro et al. (), Flachaire et al.…”
mentioning
confidence: 99%